Predicting job satisfaction and workers' intentions to leave at the bottom of the high value agricultural chain: evidence from the Ethiopian cut flower industry. Issue 9 (15th May 2018) - Staelens, Lotte; Desiere, Sam; Louche, Céline; D'Haese, Marijke
Abstract: While there is a large body of research focusing on working conditions in labour-intensive industries, none has yet considered how workers themselves perceive their own working conditions. This paper draws on a sample of workers from the cut flower sector industry in Ethiopia to examine the extent to which workers are satisfied with their jobs and to explore the relationship between job satisfaction and intention to leave. Results suggest that a positive evaluation of extrinsic organizational rewards (wage, job security and healthy environment) contributes to workers' job satisfaction. Dissatisfied workers report higher intentions to leave their job in the flower farms. In addition to low levels of job satisfaction, having alternative livelihood strategies is a key determining factor in the intention to leave. Interestingly, being a member of an informal savings net organized at the work floor mitigates the intention to leave. The paper ends with some implications for managers and policy-makers, along with limitations and suggestions for future research.